2017
DOI: 10.1002/cam4.1133
|View full text |Cite
|
Sign up to set email alerts
|

Metformin synergistic pemetrexed suppresses non‐small‐cell lung cancer cell proliferation and invasion in vitro

Abstract: The aim of this study was to investigate whether metformin in combination with pemetrexed has an effect on the treatment of non‐small‐cell lung cancer (NSCLC) models and to explore the related molecular mechanism. The half maximal inhibitory concentration (IC50) and combination index (CI) of metformin and pemetrexed were detected by the CCK8 assay to assess the antiproliferative and therapeutic effects of the two‐drug combination. Flow cytometry (FCM) and invasion assays were used to estimate the variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In murine models, combinatorial metformin treatment with the chemotherapeutic agent doxorubicin led to reduced mammary tumor mass and relapse compared to either drug alone when performing xenograft experiments ( 83 , 84 ). There is also data showing that metformin has synergistic effects with various chemotherapy agents, including Pemetrexed in cell lines of non-small cell lung cancer (NSCLC), ( 85 ) EGFR-TKI in patients with NSCLC ( 86 ), Trichostatin in osteosarcoma cell lines ( 87 ), Simvastatin in animal models of metastatic prostate cancer ( 88 ) and Nelfinavir in cervical cancer xenografts ( 89 ). It has also been suggested that metformin may lead to a re-sensitization of cancer cells that have become resistance to chemotherapy, the predominant cause of treatment failure in patients undergoing treatment ( 45 , 84 , 90 , 91 ).…”
Section: Metformin: Bioenergetic Medicinementioning
confidence: 99%
“…In murine models, combinatorial metformin treatment with the chemotherapeutic agent doxorubicin led to reduced mammary tumor mass and relapse compared to either drug alone when performing xenograft experiments ( 83 , 84 ). There is also data showing that metformin has synergistic effects with various chemotherapy agents, including Pemetrexed in cell lines of non-small cell lung cancer (NSCLC), ( 85 ) EGFR-TKI in patients with NSCLC ( 86 ), Trichostatin in osteosarcoma cell lines ( 87 ), Simvastatin in animal models of metastatic prostate cancer ( 88 ) and Nelfinavir in cervical cancer xenografts ( 89 ). It has also been suggested that metformin may lead to a re-sensitization of cancer cells that have become resistance to chemotherapy, the predominant cause of treatment failure in patients undergoing treatment ( 45 , 84 , 90 , 91 ).…”
Section: Metformin: Bioenergetic Medicinementioning
confidence: 99%
“…Even though several anticarcinogenic effects of metformin are observed, the clinical data are still contentious depending on disease-related (type of tumor, clinical stage, form of treatment) and on patient-related factors (insulin resistance, age, sex) [ 21 ]. For in vitro experiments, the combination of metformin with several chemotherapeutic agents shows controversial results ranging from synergistic effects [ 22 24 ] to even adverse effects [ 25 , 26 ]. So far, these investigations underline the need for a more detailed understanding of the molecular mechanisms that occur when combining metformin with chemotherapeutics before applying it as a potential adjuvant in chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl-2 protein family has been extensively studied among numerous apoptosis regulating factors (Ola, Nawaz, & Ahsan, 2011). Furthermore, Zhang, Feng, Li, Yi, and Li (2017) demonstrated that the combination of PTX and metformin could enhance the antitumor activity of PTX by regulating Bax and Bcl-2.…”
Section: Discussionmentioning
confidence: 99%